Решите уравнение: (х^2 - 3x - 1)^2 + 2x (x-3) = 1

aveiro1 aveiro1    2   14.08.2019 08:10    0

Ответы
MegaCrisp1 MegaCrisp1  04.10.2020 18:12
Выносим х за скобки: (x(x-3)-1)^2+2x(x-3)=1, и раскрываем их:
x^2(x-3)^2-2x(x-3)+1+2x(x-3)-1=0;
x^2(x-3)^2=0;
x^2=0; x=0;
(x-3)^2=0; x-3=0; x=3;
ответ: x1=0; x2=3
ПОКАЗАТЬ ОТВЕТЫ
ania51 ania51  04.10.2020 18:12
(х^2-3х-1)^2+2x(x-3)=1
х^4-3х^3-х^2-3х^3+9х^2+3х-х^2+3х+1+2х^2-6х=1
х^4-6х^3+9х^2+1=1
х^4-6х^3+9х^2=0
х^2(х^2-6х+9)=0
х^2(х-3)^2=0
1) х^2=0...2) (х-3)^2=0
х=0х-3=0
х=3
ПОКАЗАТЬ ОТВЕТЫ